Synthesis of Germanium Dioxide Microclusters on Silicon Substrate in Non-aqueous Solution by Electrochemical Deposition - Mastura Shafinaz Zainal Abidin; Shahjahan Shahjahan; Abdul Manaf Hashim (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
We report the formation of crystalline germanium dioxide (GeO2) microclusters on n-Si (100) electrodeposited in non-aqueous electrolyte (a mixture of 5 vol.% germanium tetrachloride (GeCl4) and dipropylene glycol (C6H14O3) ) at current density of 20 mA/cm2 for 200 sec. Pt, C and Ge are used as an anode while Si acts as a cathode. Field- emission scanning electron microscopy (FESEM) images show that the deposited GeO2 microclusters are having rounded-mushroom-shaped particles with the smallest size of 660 nm. Energy dispersive x-ray (EDX) spectra reveal that the particles are only composed of Ge and O elements. Raman spectra confirm the formation of crystalline GeO2 with trigonal bonding structures in all samples. The photoluminescence (PL) spectra show two significant emission peaks in visible range at 2.27 eV and 2.96 eV, which seems to be attributed by GeO2 and Si defects. C6H14O3 seems to contribute to the formation of GeO2 due to its hygroscopic nature. Such microcluster structures shall provide some potential applications for electronic and optical devices on Si platform.